Tinjauan Literatur Pemerdagangan dan Eksploitasi Kanak-Kanak di Asia Tenggara - Che Mohd Nasir, Norruzeyati; Kamaluddin, Mohammad Rahim (UUM Press, 2018)
Human trafficking is a modern form of slavery and organized crime that violates human rights and threatens public and national security. The International Labor Organization (ILO) estimates that there are 40.3 million people have been the victims of human trafficking, with the majority of them are women and children. Children are the most vulnerable and high risk group to be sexually exploited through child marriage and economically exploited as forced labour and beggars. The establishment of the Protocol to Prevent, Suppress and Punish Trafficking in Persons, especially Women and Children in 2000, was an international effort to combat this crime. Countries in Southeast Asia are also confronted with this crisis especially involving children and have been identified either as a source, destination or transit countries in the case of human trafficking. While the issue is very alarming, the accurate assessment of child victims is yet to be found due to the clandestine nature of the crime. There are many factors such as poverty, debt bondage, traditional practices that encourage early marriage, low level of education, fraudulent documents and collaboration between the recruiter and family, leader or related agencies have contributed significantly towards the existing child trafficking and sexual exploitation issues. This articles aims to present issues pertaining to child trafficking and exploitation. With that in mind, the current study employs library research as a research design in order to gather information from various sources such as journal articles, books, reports, and conference proceedings. It is highly expected that this article would provide exposure and in-depth understanding regarding child traffic king and exploitation to related agencies. In-depth understanding is vital to develop related policies and guidelines to curb this transnational crime.